EPC Minutes 2005-02-10 - Academic Senate:::::::::
Educational Policies Committee. Chair Report. Statewide Senator Report. Vice Chair Report. Representation on Administrative Appointment Committees policy revision – referred back to S&F. Vice President of Administration and Finance Report. Vice President of Student Affairs Report. EPC Report. FSAC Report. SAC Report. Associated Students Report. Replacement member for AVP of Academic Programs Search. Request for Accreditation input. Meeting location for rest of the semester. Follow up on OER resolution – Ad Hoc planning committee. Summer Quorum discussion. Senate agenda approved.